Sand core coating for aluminum alloy casting and preparation method of sand core coating

By using sand-core paint composed of materials such as wax, iron olivine and other materials when casting aluminum alloy castings, the problems of sand sticking, sand clamping and sand cleaning are solved, and the high quality and airtightness of the castings are achieved.

CN119657819AActive Publication Date: 2025-03-21SHANDONG HONGYUAN NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510195301.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

When casting aluminum alloy castings with complex structures, existing sand core coatings cannot effectively prevent difficulties in sand bonding, sand clamping and sand cleaning, resulting in a decrease in the quality of the castings. Intrinsic quality problems such as pores and looseness, affecting the airtightness of the castings.

Method used

The sand-core coating consisting of cerite, iron olivine, zircon powder, calcium titanate, magnesium sand, ice crystal and phosphorus pentoxide are used. Through the combination and combination of these materials, the coating resists metal liquid erosion, sand-tickness and thermal stability.

Benefits of technology

The sand core coating remains stable at high temperatures and can effectively resist metal erosion and sand sticking, improve the internal quality and airtightness of the castings, and reduce the defects and processing difficulty of the castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of sand core coating preparation, and particularly relates to a sand core coating for an aluminum alloy casting and a preparation method of the sand core coating. The sand core coating for the aluminum alloy casting consists of the following raw materials: pyrophyllite, fayalite, zircon powder, magnesia, calcium titanate, cryolite, phosphorus pentoxide, sodium pyrophosphate, rectorite, octylphenol polyoxyethylene ether, n-caprylic alcohol and water. According to the sand core coating for the aluminum alloy casting, a mixture of pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite and phosphorus pentoxide is used as a refractory material, water is used as a carrier liquid, a mixture of sodium pyrophosphate and rectorite is used as a suspending agent, and meanwhile, an n-caprylic alcohol defoaming agent and an octylphenol polyoxyethylene ether surfactant are added; the synergistic effect of the raw materials ensures that the prepared sand core coating has good molten metal scouring resistance, sand burning resistance and thermal stability during application, so that the sand core coating has excellent peel strength and refractoriness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sand core coating preparation, and specifically relates to a sand core coating for aluminum alloy castings and a preparation method thereof. Background Art

[0002] Casting coatings are generally composed of refractory materials, carrier liquids, binders, suspending agents and other additives. They are widely used in various molds and cores in casting production. They have the functions of preventing sand from sticking to castings, reducing the surface roughness of castings, increasing the service life of sand molds and improving the surface material of castings.

[0003] Casting coatings can be classified in many ways. According to the degree of refractory, they can be divided into high-refractory coatings, medium-refractory coatings and low-refractory coatings; according to the carrier liquid used, they can be divided into water-based coatings and alcohol-based coatings; according to the casting material, they can be divided into clay sand coatings, resin sand coatings, water glass sand coatings and metal coatings; according to the casting alloy material, they can be divided into cast steel coatings, cast iron coatings and non-ferrous alloy coatings, etc.

[0004] When casting water-cooled motor housing integrated curved special-shaped water channel with complex inner cavity structure and air tightness test, the complex curved special-shaped cavity cannot be processed by sandblasting, shot blasting, etc., and the cleanliness of the inner cavity is poor. Although polishing technology such as abrasive flow is applied, the original rough surface of the product water channel cannot be retained, resulting in failure to achieve cooling effect. Aluminum alloy castings with complex structures often require sand cores to form internal cavities or complex shapes. At this time, the selection of sand core coatings is particularly important. Sand core coatings can ensure that the sand core remains stable at high temperatures and does not deform or damage during the pouring of molten metal. If the sand core coating with good performance is not well selected, it will not only cause serious defects such as sand sticking and sand inclusion, but also cause difficulty in sand removal, increase the workload of cleaning and grinding, seriously affect the quality of the casting, and even make the casting scrapped. It will also affect the intrinsic quality of the casting, causing defects such as pores and looseness inside the casting, resulting in the casting failing the air tightness test after processing, that is, penetration during the pressure test.

[0005] Therefore, exploring a new type of sand core coating for aluminum alloy castings has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a sand core coating for aluminum alloy castings. The sand core coating has the properties of resistance to molten metal scouring, resistance to sand sticking and thermal stability. The present invention also provides a preparation method thereof.

[0007] The sand core coating for aluminum alloy castings of the present invention is composed of the following raw materials, measured in parts by weight: 22-24 parts of pyrophyllite, 11-13 parts of fayalite, 7.2-7.6 parts of zircon powder, 3.1-3.4 parts of magnesia, 5.1-5.5 parts of calcium titanate, 4.3-5.2 parts of cryolite, 1.5-1.7 parts of phosphorus pentoxide, 2.6-2.8 parts of sodium pyrophosphate, 3.2-3.5 parts of rectorite, 0.18-0.21 parts of octylphenol polyoxyethylene ether, 0.35-0.37 parts of n-octanol, and 24-26 parts of water.

[0008] in: The chemical composition of the pyrophyllite is as follows, in terms of mass percentage: MgO 0.76%, CaO 2.13%, Al2O3 15.89%, SiO2 76.37%, Fe2O3 0.41%, P2O5 0.67%, K2O 0.36%, Na2O 0.05%, and the loss on ignition is 3.36%.

[0009] The chemical composition of the fayalite, in terms of mass percentage, is as follows: FeO 67.59%, SiO2 24.52%, MgO 2.54%, Al2O3 0.21%, TiO2 0.03%, CaO 0.32%, K2O 0.03%, Na2O 0.02%, P2O5 0.01%, and the loss on ignition is 4.73%.

[0010] The chemical composition of the magnesia is as follows, in terms of mass percentage: SiO2 9.32%, Al2O3 1.45%, MgO72.65%, Fe2O3 0.58%, CaO 5.32%, SO30.12%, and loss on ignition is 10.56%.

[0011] Preferably, the sand core coating for aluminum alloy castings described in the present invention is composed of the following raw materials, in parts by weight: 23 parts of pyrophyllite, 12 parts of fayalite, 7.4 parts of zircon powder, 3.3 parts of magnesia, 5.3 parts of calcium titanate, 4.8 parts of cryolite, 1.6 parts of phosphorus pentoxide, 2.7 parts of sodium pyrophosphate, 3.3 parts of rectorite, 0.20 parts of octylphenol polyoxyethylene ether, 0.36 parts of n-octanol, and 25 parts of water.

[0012] The sand core coating for aluminum alloy castings described in the present invention uses a mixture of pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite powder and phosphorus pentoxide as a refractory material, so that the sand core coating has resistance to molten metal scouring, resistance to sand adhesion and thermal stability. Among them, pyrophyllite and fayalite are used in combination to ensure that the prepared sand core coating has resistance to molten metal scouring. The main component of pyrophyllite is aluminum silicate, and pyrophyllite can form a silicate melt after contacting with molten metal at high temperature, thereby enhancing the resistance of the sand core coating to molten metal; while the main component of fayalite is iron silicate, which has a relatively dense crystal structure and shows high inertness in high temperature and chemical corrosion environments, so its addition can further improve the resistance of the sand core coating to molten metal scouring. Zircon powder, magnesia and calcium titanate are used in combination to ensure the sand core coating's resistance to sand adhesion, thermal stability and chemical stability. Among them, the high refractoriness and low thermal expansion of zircon powder enable it to remain stable at high temperatures, and its high thermal conductivity can quickly conduct heat to the casting, thereby reducing the contact time between the molten metal and the sand core, and thus making the sand core coating resistant to sand sticking. The crystal structure of calcium titanate helps to form a dense coating, enhance the mechanical strength and thermal stability of the coating, and its stable chemical properties enable it to resist the erosion of molten metal in a high temperature environment, thereby reducing chemical sand sticking. The chemical inertness of magnesia sand makes it difficult to react with molten metal at high temperatures, thereby reducing mechanical and chemical sand sticking. At the same time, its own high wear resistance enables it to resist the scouring of molten metal and reduce the wear of the sand core surface. Therefore, pyrophyllite, fayalite, zircon powder, calcium titanate and magnesia sand are used in combination to ensure the resistance to molten metal scouring, anti-sand sticking and stability of the prepared sand core coating. In addition, cryolite and phosphorus pentoxide are added to the refractory material described in this application. The addition of cryolite and phosphorus pentoxide can improve the fluidity of the sand core coating and form a denser structure at high temperature through the filling effect, thereby further improving the comprehensive performance of the sand core coating.

[0013] In addition, the sand core coating for aluminum alloy castings described in the present application uses a mixture of sodium pyrophosphate and rectorite as a suspending agent. Sodium pyrophosphate increases the electrostatic repulsion between particles to keep the particles suspended in the carrier liquid. The layered structure of rectorite can make the solid particles in the sand core coating evenly distributed and improve the adhesion of the sand core coating. Octylphenol polyoxyethylene ether is used as a surfactant to reduce the surface tension of the sand core coating, and n-octanol defoaming agent is added.

[0014] The method for preparing the sand core coating for aluminum alloy castings of the present invention comprises the following steps: (1) grinding pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite, phosphorus pentoxide, sodium pyrophosphate and rectorite, and passing the mixture through a 1500-mesh sieve to prepare a first mixture; (2) mixing octylphenol polyoxyethylene ether and water, then adding the first mixture prepared in step (1), and continuously stirring and mixing for 65-70 minutes to prepare a second mixture; (3) Add n-octanol to the second mixture prepared in step (2), and continue stirring and mixing for 40-45 minutes to prepare a sand core coating for aluminum alloy castings.

[0015] in: The stirring speed in step (2) is 500-550 r / min.

[0016] The stirring speed in step (3) is 1000-1100 r / min.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The sand core coating for aluminum alloy castings described in the present invention uses a mixture of pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite and phosphorus pentoxide as refractory materials, water as a carrier liquid, a mixture of sodium pyrophosphate and rectorite as a suspending agent, and n-octanol defoaming agent and octylphenol polyoxyethylene ether surfactant are added. The synergistic effect between the raw materials ensures that the prepared sand core coating has good resistance to metal liquid erosion, anti-sand adhesion and thermal stability when used, so that the sand core coating has excellent peeling strength and refractoriness.

[0018] (2) The method for preparing the sand core coating for aluminum alloy castings described in the present invention has a simple production process, is easy to operate, has high production efficiency, high quality of finished products, and stable comprehensive performance. DETAILED DESCRIPTION

[0019] The present invention is further described below with reference to the embodiments.

[0020] Example 1 The sand core coating for aluminum alloy castings described in Example 1 is composed of the following raw materials, in parts by weight: 23 parts of pyrophyllite, 12 parts of fayalite, 7.4 parts of zircon powder, 3.3 parts of magnesia, 5.3 parts of calcium titanate, 4.8 parts of cryolite, 1.6 parts of phosphorus pentoxide, 2.7 parts of sodium pyrophosphate, 3.3 parts of rectorite, 0.20 parts of octylphenol polyoxyethylene ether, 0.36 parts of n-octanol, and 25 parts of water.

[0021] in: The chemical composition of the pyrophyllite is as follows, in terms of mass percentage: MgO 0.76%, CaO 2.13%, Al2O3 15.89%, SiO2 76.37%, Fe2O3 0.41%, P2O5 0.67%, K2O 0.36%, Na2O 0.05%, and the loss on ignition is 3.36%.

[0022] The chemical composition of the fayalite, in terms of mass percentage, is as follows: FeO 67.59%, SiO2 24.52%, MgO 2.54%, Al2O3 0.21%, TiO2 0.03%, CaO 0.32%, K2O 0.03%, Na2O 0.02%, P2O5 0.01%, and the loss on ignition is 4.73%.

[0023] The chemical composition of the magnesia is as follows, in terms of mass percentage: SiO2 9.32%, Al2O3 1.45%, MgO72.65%, Fe2O3 0.58%, CaO 5.32%, SO30.12%, and loss on ignition is 10.56%.

[0024] The method for preparing the sand core coating for aluminum alloy castings described in Example 1 comprises the following steps: (1) grinding pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite, phosphorus pentoxide, sodium pyrophosphate and rectorite, and passing the mixture through a 1500-mesh sieve to prepare a first mixture; (2) mixing octylphenol polyoxyethylene ether and water, then adding the first mixture prepared in step (1), and continuously stirring and mixing for 65 minutes to prepare a second mixture; (3) n-octanol was added to the second mixture prepared in step (2), and the mixture was stirred and mixed for 43 minutes to prepare a sand core coating for aluminum alloy castings.

[0025] in: The stirring speed in step (2) is 525 r / min.

[0026] The stirring speed in step (3) is 1050 r / min.

[0027] Example 2 The sand core coating for aluminum alloy castings described in this Example 2 is composed of the following raw materials, in parts by weight: 24 parts of pyrophyllite, 11 parts of fayalite, 7.2 parts of zircon powder, 3.4 parts of magnesia, 5.1 parts of calcium titanate, 5.2 parts of cryolite, 1.5 parts of phosphorus pentoxide, 2.6 parts of sodium pyrophosphate, 3.5 parts of rectorite, 0.18 parts of octylphenol polyoxyethylene ether, 0.37 parts of n-octanol, and 26 parts of water.

[0028] in: The chemical composition of the pyrophyllite is as follows, in terms of mass percentage: MgO 0.76%, CaO 2.13%, Al2O3 15.89%, SiO2 76.37%, Fe2O3 0.41%, P2O5 0.67%, K2O 0.36%, Na2O 0.05%, and the loss on ignition is 3.36%.

[0029] The chemical composition of the fayalite, in terms of mass percentage, is as follows: FeO 67.59%, SiO2 24.52%, MgO 2.54%, Al2O3 0.21%, TiO2 0.03%, CaO 0.32%, K2O 0.03%, Na2O 0.02%, P2O5 0.01%, and the loss on ignition is 4.73%.

[0030] The chemical composition of the magnesia is as follows, in terms of mass percentage: SiO2 9.32%, Al2O3 1.45%, MgO72.65%, Fe2O3 0.58%, CaO 5.32%, SO30.12%, and loss on ignition is 10.56%.

[0031] The method for preparing the sand core coating for aluminum alloy castings described in this embodiment 2 comprises the following steps: (1) grinding pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite, phosphorus pentoxide, sodium pyrophosphate and rectorite, and passing the mixture through a 1500-mesh sieve to prepare a first mixture; (2) mixing octylphenol polyoxyethylene ether and water, then adding the first mixture prepared in step (1), and continuously stirring and mixing for 70 minutes to prepare a second mixture; (3) Add n-octanol to the second mixture prepared in step (2), and continue stirring and mixing for 40 minutes to prepare a sand core coating for aluminum alloy castings.

[0032] in: The stirring speed in step (2) is 500 r / min.

[0033] The stirring speed in step (3) is 1100 r / min.

[0034] Example 3 The sand core coating for aluminum alloy castings described in this Example 3 is composed of the following raw materials, in parts by weight: 22 parts of pyrophyllite, 13 parts of fayalite, 7.6 parts of zircon powder, 3.1 parts of magnesia, 5.5 parts of calcium titanate, 4.3 parts of cryolite, 1.7 parts of phosphorus pentoxide, 2.8 parts of sodium pyrophosphate, 3.2 parts of rectorite, 0.21 parts of octylphenol polyoxyethylene ether, 0.35 parts of n-octanol, and 24 parts of water.

[0035] in: The chemical composition of the pyrophyllite is as follows, in terms of mass percentage: MgO 0.76%, CaO 2.13%, Al2O3 15.89%, SiO2 76.37%, Fe2O3 0.41%, P2O5 0.67%, K2O 0.36%, Na2O 0.05%, and the loss on ignition is 3.36%.

[0036] The chemical composition of the fayalite, in terms of mass percentage, is as follows: FeO 67.59%, SiO2 24.52%, MgO 2.54%, Al2O3 0.21%, TiO2 0.03%, CaO 0.32%, K2O 0.03%, Na2O 0.02%, P2O5 0.01%, and the loss on ignition is 4.73%.

[0037] The chemical composition of the magnesia is as follows, in terms of mass percentage: SiO2 9.32%, Al2O3 1.45%, MgO72.65%, Fe2O3 0.58%, CaO 5.32%, SO30.12%, and loss on ignition is 10.56%.

[0038] The method for preparing the sand core coating for aluminum alloy castings described in Example 3 is composed of the following steps: (1) grinding pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite, phosphorus pentoxide, sodium pyrophosphate and rectorite, and passing the mixture through a 1500-mesh sieve to prepare a first mixture; (2) mixing octylphenol polyoxyethylene ether and water, then adding the first mixture prepared in step (1), and continuously stirring and mixing for 65 minutes to prepare a second mixture; (3) Add n-octanol to the second mixture prepared in step (2), and continue stirring and mixing for 45 minutes to prepare a sand core coating for aluminum alloy castings.

[0039] in: The stirring speed in step (2) is 550 r / min.

[0040] The stirring speed in step (3) is 1000 r / min.

[0041] Comparative Example 1 The preparation method of the sand core coating for aluminum alloy castings described in this comparative example 1 is the same as that of Example 1, and the only difference is that the raw material composition is different. The sand core coating for aluminum alloy castings described in this comparative example 1 is composed of the following raw materials in parts by weight: 12 parts of fayalite, 7.4 parts of zircon powder, 3.3 parts of magnesia, 5.3 parts of calcium titanate, 4.8 parts of cryolite, 1.6 parts of phosphorus pentoxide, 2.7 parts of sodium pyrophosphate, 3.3 parts of rectorite, 0.20 parts of octylphenol polyoxyethylene ether, 0.36 parts of n-octanol, and 25 parts of water.

[0042] Comparative Example 2 The preparation method of the sand core coating for aluminum alloy castings described in this comparative example 2 is the same as that of Example 1, and the only difference is that the raw material composition is different. The sand core coating for aluminum alloy castings described in this comparative example 2 is composed of the following raw materials in parts by weight: 23 parts of pyrophyllite, 7.4 parts of zircon powder, 3.3 parts of magnesia, 5.3 parts of calcium titanate, 4.8 parts of cryolite, 1.6 parts of phosphorus pentoxide, 2.7 parts of sodium pyrophosphate, 3.3 parts of rectorite, 0.20 parts of octylphenol polyoxyethylene ether, 0.36 parts of n-octanol, and 25 parts of water.

[0043] Comparative Example 3 The preparation method of the sand core coating for aluminum alloy castings described in this comparative example 3 is the same as that of Example 1, and the only difference is that the raw material composition is different. The sand core coating for aluminum alloy castings described in this comparative example 3 is composed of the following raw materials in parts by weight: 23 parts of pyrophyllite, 12 parts of fayalite, 4.8 parts of cryolite, 1.6 parts of phosphorus pentoxide, 2.7 parts of sodium pyrophosphate, 3.3 parts of rectorite, 0.20 parts of octylphenol polyoxyethylene ether, 0.36 parts of n-octanol, and 25 parts of water.

[0044] 100 kg of the sand core coating prepared in Examples 1-3 and Comparative Examples 1-3 was added to a coating mixer, and then 25 kg of pure water was added, and the mixture was stirred evenly for 30 minutes. The stirred sand core coating was then filtered through an 80-mesh filter and flowed into a coating dipping pool. The Baume degree was controlled to be 38. The sand core was immersed in the sand core coating dipping pool and stayed there for 4 seconds. The sand core coating was evenly dipped onto the surface of the sand core, and the coating was even. The sand core was placed in a drying furnace and dried before low-pressure casting of aluminum alloy. The sand core coating prepared in Examples 1-3 and Comparative Examples 1-3 was tested for performance, and the results are shown in Table 1 below: Table 1 Performance test results of sand core coatings prepared in Examples 1-3 and Comparative Examples 1-3

[0045] It can be seen from the data recorded in Table 1 that the sand core coating for aluminum alloy castings prepared in the present invention has excellent peel strength and refractoriness, and its application can ensure the internal quality of the casting. Therefore, it is reflected from the side that the sand core coating prepared in the present invention has excellent resistance to molten metal erosion, resistance to sand adhesion and stability.

Claims

1. A sand core coating for aluminum alloy castings, characterized in that: The invention is composed of the following raw materials in parts by weight: 22-24 parts of pyrophyllite, 11-13 parts of fayalite, 7.2-7.6 parts of zircon powder, 3.1-3.4 parts of magnesia, 5.1-5.5 parts of calcium titanate, 4.3-5.2 parts of cryolite, 1.5-1.7 parts of phosphorus pentoxide, 2.6-2.8 parts of sodium pyrophosphate, 3.2-3.5 parts of rectorite, 0.18-0.21 parts of octylphenol polyoxyethylene ether, 0.35-0.37 parts of n-octanol and 24-26 parts of water.

2. The sand core coating for aluminum alloy castings according to claim 1, characterized in that: The chemical composition of the pyrophyllite is as follows, in terms of mass percentage: MgO 0.76%, CaO 2.13%, Al2O3 15.89%, SiO2 76.37%, Fe2O30.41%, P2O5 0.67%, K2O 0.36%, Na2O 0.05%, and the loss on ignition is 3.36%.

3. The sand core coating for aluminum alloy castings according to claim 1, characterized in that: The chemical composition of the fayalite, in terms of mass percentage, is as follows: FeO 67.59%, SiO2 24.52%, MgO 2.54%, Al2O3 0.21%, TiO2 0.03%, CaO 0.32%, K2O 0.03%, Na2O 0.02%, P2O5 0.01%, and the loss on ignition is 4.73%.

4. The sand core coating for aluminum alloy castings according to claim 1, characterized in that: The chemical composition of the magnesia is as follows, in terms of mass percentage: SiO2 9.32%, Al2O3 1.45%, MgO 72.65%, Fe2O3 0.58%, CaO 5.32%, SO3 0.12%, and the loss on ignition is 10.56%.

5. The sand core coating for aluminum alloy castings according to claim 1, characterized in that: The invention is composed of the following raw materials in parts by weight: 23 parts of pyrophyllite, 12 parts of fayalite, 7.4 parts of zircon powder, 3.3 parts of magnesia, 5.3 parts of calcium titanate, 4.8 parts of cryolite, 1.6 parts of phosphorus pentoxide, 2.7 parts of sodium pyrophosphate, 3.3 parts of rectorite, 0.20 parts of octylphenol polyoxyethylene ether, 0.36 parts of n-octanol and 25 parts of water.

6. A method for preparing a sand core coating for aluminum alloy castings according to claim 1, characterized in that: It consists of the following steps: (1) grinding pyrophyllite, fayalite, zircon powder, calcium titanate, magnesia, cryolite, phosphorus pentoxide, sodium pyrophosphate and rectorite, and passing the mixture through a 1500-mesh sieve to prepare a first mixture; (2) mixing octylphenol polyoxyethylene ether and water, then adding the first mixture prepared in step (1), and continuously stirring and mixing for 65-70 minutes to prepare a second mixture; (3) Add n-octanol to the second mixture prepared in step (2), and continue stirring and mixing for 40-45 minutes to prepare a sand core coating for aluminum alloy castings.

7. The method for preparing a sand core coating for aluminum alloy castings according to claim 6, characterized in that: The stirring speed in step (2) is 500-550 r / min.

8. The method for preparing a sand core coating for aluminum alloy castings according to claim 6, characterized in that: The stirring speed in step (3) is 1000-1100 r / min.

Citation Information

Patent Citations

  • Pyrophillite lost foam casting coating and preparation method thereof

    CN101444827A

  • Water-based self-drying / quick-drying sand type casting coating and preparation method thereof

    CN103878302A

  • Castable used for RH refining furnace lining and construction method thereof

    CN104418597A

  • Coating for casting sand mold

    CN107511449A

  • Coating compounds for casting moulds and cores that prevent reaction gas defects

    US20100224755A1